2015
DOI: 10.1186/s12890-015-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of allergic rhinitis on the management of asthma in a working population

Abstract: BackgroundCurrently, little data is available about the management of asthma in the working population. The aim of this study was to describe asthma control and severity among workers according to current or previous allergic rhinitis comorbidity.MethodsA network of occupational physicians participated in this pilot study on a voluntary basis. They included a random sample of salaried workers during their systematic occupational medical check-up. All subjects completed a self-administered questionnaire based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Their review of 2010 provided guidelines for the diagnosis and treatment of AR and of clinical practices for the management of comorbidities of AR and asthma based on the Grading of Recommendations Assessment, Development and Evaluation method ( 3 ). ARIA has been popularized and implemented in >50 countries ( 4 , 5 ). An increasing amount of research on ‘airway consistency’ has been performed, including epidemiology, pathology, clinical diagnosis and treatment ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their review of 2010 provided guidelines for the diagnosis and treatment of AR and of clinical practices for the management of comorbidities of AR and asthma based on the Grading of Recommendations Assessment, Development and Evaluation method ( 3 ). ARIA has been popularized and implemented in >50 countries ( 4 , 5 ). An increasing amount of research on ‘airway consistency’ has been performed, including epidemiology, pathology, clinical diagnosis and treatment ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Allergic rhinitis subjects have been found to have a 3-fold increased risk of asthma compared to subjects without allergic rhinitis (23.8 and 7.5%, respectively) [ 30 ]. A study by Dorothée Provost et al among the French working population revealed that 72.5% of current asthmatics had allergic rhinitis [ 31 ]. In a review, Mike Thomas stated that allergic rhinitis is very common in patients with asthma, with a reported prevalence of up to 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic rhinitis (AR) is a type of nasal mucosa inflammatory disease, with itching, sneezing, runny nose, and congestion, and is caused by immunoglobulin E (IgE)‐mediated reactions to inhaled allergens (Greiner et al, 2011). AR affects 10%–40% of the global population, and 15%–38% of the cases have asthma as a comorbidity, suggesting AR may be an independent risk factor for asthma (Provost et al, 2015). The prevalence of AR is estimated to be a great economic burden (Bernstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%